ChatGPT for research and publication: Opportunities and challenges (Journal of Applied Learning and Teaching, 2023)
This position paper explores the potential opportunities and challenges in the adoption of OpenAI’s ChatGPT for scholarly research and publication. ChatGPT was launched in November 2022 for public use, and it has already garnered enormous attention for a variety of applications in academia. Researchers are adopting ChatGPT at different stages of research including idea generation, summarizing literature, and manuscript preparation. Notably, several research articles have even attributed authorship to ChatGPT, sparking a new debate on the role of AI in authorship. We contend that ChatGPT has far-reaching implications for scholarly research and publication going forward. In this paper, we investigate its current use in contemporary research and based on this we outline the opportunities that ChatGPT could potentially offer. We believe that ChatGPT could be leveraged by researchers, journal editors, and reviewers to make the research and publication process more efficient. Later, we discuss the challenges and concerns exposed by ChatGPT that require immediate attention such as AI authorship, unintentional plagiarism, nonexistent references, and threats of international inequalities. We conclude with optimistic expectations for ChatGPT adoption in research in the future.